(untitled) - Byars, Betsy Cromer; Howard, Arthur; Myers, Laurie; Duffey, Betsy (Henry Holt, 2004)
The students in Mr. Magro's class submit stories for the SOS file about their biggest emergencies, and then they read them aloud for extra credit.
Keywords: Storytelling; Fiction; Schools; Fiction